537 Feedback after child protection medicals – keeping up with RCPCH standards. (17th August 2022) - Baker, Robyn; Howsam, Frankie
Abstract : Aims: In October 2020 the RCPCH released a new set of standards for child protection medical assessments. These highlight the importance of actively seeking feedback from service users and families to ensure we are delivering the best care. It is an integral part of reviewing the service we provide, however, obtaining this feedback at such an emotional time can be challenging in practice. Standard 12: 'Regular review of the quality of the child protection medical assessment service' . 1 RCPCH recommends regular monitoring of the service, ideally annually. This should include feedback from children and families who have undergone assessments. We surveyed safeguarding teams around the UK to determine how they comply with the standards. We plan to utilize their experience to develop new strategies for obtaining feedback in our trust. Methods: We contacted safeguarding teams from trusts around the UK by email with a survey about their process for collecting feedback and reviewing their service. We asked: Do you routinely get feedback following child protection medicals? If so, how? Who collects this feedback? Do you do this immediately after a medical assessment or later? Do you annually assess your service? If so, how? Results: We contacted 60 safeguarding teams and received 22 responses. Of the 22 trusts polled, 17 attempted to collect feedback. However, only 2 of these trusts did it routinely after every assessment. 5 did not collect any feedback. Of the trusts that did seek feedback, the majority used a feedback form (47%), whilst others asked for verbal feedback (29%), and the remainder did a combination of both. We found that most trusts used the safeguarding team to collect the feedback, or a combination of safeguarding team and social worker, asking at different times (see table 1 ). The majority of trusts also reported they sought feedback either immediately after, or within one week of the assessment (see table 2 ). We also asked whether trusts annually assessed their child protection medical service. 64% of trusts do, which is usually done by audit. Several trusts mentioned that they have had difficulty complying with this standard and reported they had attempted to get feedback but didn't receive any. Conclusion: In conclusion, most trusts we surveyed are not routinely getting feedback from children and families following the child protection medical assessment. This survey has demonstrated the difficulties safeguarding teams face when trying to comply with the RCPCH standards. Trusts that do request feedback often employ multiple strategies to achieve this, with different members of the MDT using a combination of methods at various points in time. We can use their experience to help develop a standardized system in our own trust and using this feedback to improve the service we provide to children. Reference: Good practice service delivery standards for the management of children referred for child protection medical assessments, RCPCH